Adult chicken alpha-globin gene expression in transfected QT6 quail cells: evidence for a negative regulatory element in the alpha D gene region. - Lewis, W (1991)
The chicken adult alpha-globin genes, alpha A and alpha D, are closely linked in chromosomal DNA and are coordinately expressed in vivo in an approximate 3:1 ratio, respectively. When subcloned DNAs containing one or the other gene are stably transfected into QT6 quail fibroblasts, the alpha A-globin gene is expressed at measurable RNA levels, but the alpha D gene is not. The alpha A gene expression can be considerably increased by the presence of a linked Rous sarcoma virus long terminal repeat enhancer, but that of the alpha D gene remains undetectable. Transfection with subclones containing both genes, either in cis or in trans, leads to considerably reduced alpha A RNA levels and still no observable alpha D gene expression. Transfection with deleted subclones suggests that maximal expression levels in this system require the alpha A-globin gene promoter, as opposed to that of the alpha D gene, but that such expression is greatly reduced by one or more DNA sequences which lie approximately 2,000 base pairs upstream of the alpha A gene, within the body of the alpha D gene.